The Effects of Prior Exposure on Face Processing in Younger and Older Adults - Heisz, Jennifer J.; Ryan, Jennifer D. (Frontiers in Aging Neuroscience, 2011)
Older adults differ from their younger counterparts in the way they view faces. We assessed whether older adults can use past experience to mitigate these typical face-processing differences; that is, we examined whether there are age-related differences in the use of memory to support current processing. Eye movements of older and younger adults were monitored as they viewed faces that varied in the type/amount of prior exposure. Prior exposure was manipulated by including famous and novel faces, and by presenting faces up to five times. We expected that older adults may have difficulty quickly establishing new representations to aid in the processing of recently presented faces, but would be able to invoke face representations that have been stored in memory long ago to aid in the processing of famous faces. Indeed, younger adults displayed effects of recent exposure with a decrease in the total fixations to the faces and a gradual increase in the proportion of fixations to the eyes. These effects of recent exposure were largely absent in older adults. In contrast, the effect of fame, revealed by a subtle increase in fixations to the inner features of famous compared to non-famous faces, was similar for younger and older adults. Our results suggest that older adults’ current processing can benefit from lifetime experience, however the full benefit of recent experience on face processing is not realized in older adults.